The Roman City of Tarsus in Cilicia and its Terracotta Figurines - Isabelle Hasselin Rous; Serdar Yalçin (Les Carnets de l’ACoSt)
From the Bronze Age to Greco-Roman antiquity, Tarsus was an important urban center because of its proximity to the famous Cilician Gates that connected central Anatolia to the Mediterranean coast and northern Syria, as well its maritime connections to the eastern Mediterranean through its harbor. The mound of Gözlükule, the oldest and continuously inhabited part of the ancient city, informs modern scholarship about the material and visual culture of Roman Tarsus, as well as the earlier periods of habitation. The mound was explored in the middle of the 19th century, excavated in the mid-20th, and for the last 10 years was the focus of renewed excavations by the Boğazici University. During the course of all these investigations a number of deposits of Roman terracotta figurines was brought to light. This rich coroplastic material shows the evolution of a coroplastic typology according to changes in the occupation of this city from the early Imperial to the late Imperial eras. It also reveals new aspects of coroplastic production and use in the city of Tarsus, demonstrating the importance of these figurines for provincial Roman religion, especially in the transitional period of the late Roman Empire2.